“It's very much how you define dangerous”: The cultural construction of mothers' beliefs about risk in Denmark and the United States - Chris J. Boyatzis; Kylie Brandt King; Michelle Doak; Lindsay A. Zajac (Acta Psychologica)
Cultural norms influence parents' perceptions of risk. This study used a mixed-methods approach for a novel comparison of mothers' views of risk between two cultures, the United States and Denmark, that have rather different ideologies about parenting and children's rights. Mothers in the United States (n = 44, M age = 36 years) and Denmark (n = 30, M age 37 years) with children between the ages of 2 and 12 provided reactions to a photo-reaction task in which they expressed their comfort with their child in various situations of potential risk (e.g., climbing high in a tree, using sharp objects). Mothers were then interviewed to further explore their views on risk. As predicted, in the photo-reaction task U.S. mothers were significantly more uncomfortable than Danish mothers with their children in risky situations. In interviews, U.S. mothers were significantly more likely than Danish mothers to mention monitoring their children and to express anxiety about potentially risky behavior (e.g., bicycle riding, using tools such as knives and saws). In contrast, Danish mothers were more likely to describe preparing and training their children to navigate risky activities. Both groups of mothers believed that children benefit from minor accidents from risky play but differed on whether their cultures had culturally-normative risk perception: Danish mothers described cultural consistency among Danish parents whereas U.S. mothers were more likely to describe differences in fellow Americans. The findings illuminate the cultural construction of risk and how parenting ideologies are influenced by cultural demographics and support for parents.